2017
DOI: 10.3389/fimmu.2017.00536
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Activity of a Mesenchymal Stem Cell Line Stably Secreting a Tumor-Targeted TNF-Related Apoptosis-Inducing Ligand Fusion Protein

Abstract: Mesenchymal stem cells (MSCs) are currently exploited as gene delivery systems for transient in situ expression of cancer therapeutics. As an alternative to the prevailing viral expression, we here describe a murine MSC line stably expressing a therapeutic protein for up to 42 passages, yet fully maintaining MSC features. Because of superior antitumoral activity of hexavalent TNF-related apoptosis-inducing ligand (TRAIL) formats and the advantage of a tumor-targeted action, we choose expression of a dimeric EG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 51 publications
1
12
0
Order By: Relevance
“…These pathways are important in the biology of DC and T cells 56 , 57 and future work will establish if uterine g1 ILCs require these pathways and whether their differentiation is modulated by metabolism. In a recent study, Srebp proteins and genes involved in fatty-acid and cholesterol synthesis appeared essential for the metabolic reprogramming of NK cells in response to cytokine stimulation 58 , 59 . Interestingly, our analysis reveals that uterine, not liver resident g1 ILCs upregulate Slc16a13 , which encodes lactate and pyruvate cell exporter MCT13 37 .…”
Section: Disscussionmentioning
confidence: 99%
“…These pathways are important in the biology of DC and T cells 56 , 57 and future work will establish if uterine g1 ILCs require these pathways and whether their differentiation is modulated by metabolism. In a recent study, Srebp proteins and genes involved in fatty-acid and cholesterol synthesis appeared essential for the metabolic reprogramming of NK cells in response to cytokine stimulation 58 , 59 . Interestingly, our analysis reveals that uterine, not liver resident g1 ILCs upregulate Slc16a13 , which encodes lactate and pyruvate cell exporter MCT13 37 .…”
Section: Disscussionmentioning
confidence: 99%
“…They may be genetically engineered to express anti-proliferative, anti-angiogenic, pro-apoptotic factors as well as cytokines and suicide genes. Recently, Marini et al reported the therapeutic activity of MSC stably transfected to express a TNF-Related Apoptosis-Inducing Ligand (TRAIL)-EGFR specific against Colo205 xenograft tumor model [ 116 ]. Similarly, when MSC expressing TRAIL were injected in pre-established Ewing's Sarcoma mouse model they caused significant tumor apoptosis and showed anti-angiogenic function respect to control group [ 117 ].…”
Section: Mesenchymal Stem Cells As Vehicles For Cell-based Cancer Thementioning
confidence: 99%
“…Furthermore, the localized action of TRAIL delivered by MSCs appeared to bypass the resistance of cancer cells, such as breast and colorectal, to soluble TRAIL (68,69). More recently, a stable MSC line expressing a highly bioactive form of TRAIL was generated and demonstrated a significant tumor regression in an in vivo Colo205 mouse xenograft tumor model (13). The advantage of our model is that DPSCs differentiated in osteogenic conditions, expressed high levels of endogenous TRAIL, thus this system did not require any transfection technology and the cells were resistant to TRAIL-mediated apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, two studies have reported the antitumor activity of human genetically modified MSCs expressing antibodies in a diabody format (22,23). Recently, a MSC line, stably producing TRAIL which is activated in a xenotransplantation tumor model, has been generated (13). Although the main known source of MSCs is the bone marrow, a wide variety of MSCs have been recognized in dental tissues such as pulp, periodontal ligament and apical papilla, exhibiting several multilineage potencies including osteogenic, adipogenic and neurogenic (24)(25)(26)(27)(28)(29)(30), besides the expected odontogenic (31).…”
Section: Introductionmentioning
confidence: 99%